Spanish Adaptation of Motivational Climate in Education Scale with University Students - Antonio Granero-Gallegos; María Carrasco-Poyatos (MDPI AG, 2020)
The aim of this study was to provide evidence of the validity and reliability of the dimensionality of the Spanish adaptation of two correlated subscales to assess motivational climate in the university education context: Mastery motivational climate and performance motivational climate. Two different studies with cross-sectional design and different samples of university students were used to accomplish this research (Study 1: 181 students, mean age = 20.83, SD = 1.76; Study 2: 354 students, mean age = 21.84; SD = 1.98). In Study 1, Exploratory Structural Equation Modeling, Confirmatory Factor Analysis (CFA), and reliability analysis of the scale were conducted. In Study 2, CFA, reliability analysis, discriminant validity, temporal stability, factorial invariance across gender, and nomological validity were managed through a regression model measuring the relationships between democratic and autocratic behavior, mastery climate, and performance climate. The final version of the Motivational Climate in Education Scale showed acceptable goodness of fit and values of discriminant validity, reliability, temporal stability, and invariance across gender. According to its nomological validity, democratic behavior was shown to be a statistically significant predictor of mastery climate, and the teacher's autocratic behavior was shown to be a statistically significant predictor of performance climate. This scale is a valid and reliable instrument to assess mastery climate and performance climate in the Spanish university educational context.